PENGARUH PREFERENSI KONSUMEN TERHADAP KEPUTUSAN MEMILIH JASA TRANSPORTASI KERETA API CUT MEUTIA DI STASIUN COT SEURANI, KRUENG MANE KECAMATAN MUARA BATU KABUPATEN ACEH UTARA - Khalisa, Usnul; Siregar, Widyana Verawaty; Bachri, Naufal; Biby, Sapna (Faculty of economcs Universitas Singaperbangsa Karawang, 2023)
This study examined the influence of consumer preferences on the decision to choose the Cut Meutia rail transportation service at Cot Seurani station, Krueng Mane, Muara Batu subdistrict, North Aceh Regency. This study used primary data obtained by distributing questionnaires to 185 respondents selected using purposive sampling. The data analysis method used was the factorial test analysis method and the multiple linear regression analysis methods with the help of SPSS. The results of partial test for factor 1 showed that security, word of mouth, brand image, and lifestyle positively and significantly influenced the decision to use Cut Meutia Railway transportation services, and factor 2 showed that price and service quality positively and significantly influenced the decision to choose the Cut Meutia Railway transportation service. Factor 1 and factor 2 simultaneously had a positive and significant effect on the decision to use Cut Meutia Railway transportation services at Cot Seurani station, Krueng Mane, Muara Batu subdistrict, North Aceh Regency.